PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR - Halim, Angela; Yuniarwati, Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to obtain empirical evidence regarding the effect of independent commissioners, audit committees, institutional ownership and managerial ownership on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The sample selection technique in this study used purposive sampling method. The total sample used is as many as 20 selected companies for 3 years. The data in this study were processed using the SPSS version 25 program and the data source used was secondary data obtained through the official website of the Indonesia Stock Exchange (IDX) at www.idx.co.id. The results showed that the independent board of commissioners had a significant effect, while managerial ownership, institutional ownership and the audit committee had no significant effect on tax avoidance.